Cortometraje animado 2d como estrategia para promover la cultura de los artesanos alfareros de San Luis, en la provincia de Chimborazo - Cedeño Diaz, Anthonny Andres (2025)
The research addressed the progressive loss of the pottery tradition in the parish of San Luis, Chimborazo province, caused by modernization, lack of cultural dissemination, and limited interest among younger generations. The main objective was to develop a 2D animated short film as a strategy to promote and preserve the culture of artisan potters in the area. A mixed approach was applied with descriptive, exploratory, and applied design, using surveys, interviews, and observation sheets aimed at artisans and local residents. The results showed limited knowledge about the cultural value of pottery and high acceptance of animation as a means of education and cultural awareness. Using the Design Thinking methodology, an innovative audiovisual proposal was developed based on the principles of 2D animation and transmedia storytelling, which seeks to connect tradition with contemporary audiences. It was concluded that animation is an effective resource for rescuing cultural practices, strengthening community identity, and promoting community participation in the conservation of San Luis's artisan heritage.